The Five-Factor Framework: A New Approach to Analyzing Public Benefits in Fair Use Cases - Berlowitz, Joshua (The Columbia Journal of Law & the Arts, 2023)
Fair use is among “the most troublesome [doctrines] in the whole law of copyright.” Despite being one of the primary defenses against a claim of copyright infringement, the doctrine is confusingly unpredictable, providing copyright users little ex ante certainty about the lawfulness of their actions. Unfortunately, the Supreme Court’s latest fair use pronouncement may only further muddle the doctrine. In Google, LLC v. Oracle America, Inc., the Supreme Court accepted Google’s fair use defense for its appropriation of Oracle’s copyrighted code. In reaching that conclusion, Justice Breyer made a few unusual moves in his majority opinion. First, he “sidestep[ped]” the threshold question of the allegedly copyrighted work’s copyrightability. Second, he contemplated the four fair use factors out of their statutory order. Finally, his analysis of the fourth factor incorporated public benefits as an unconventional market effect. This Note argues that, of these jurisprudential choices, the last—explicit recognition of public benefits’ relevance to fair use—is likely to have an outsize impact on future cases. It further contends that Justice Breyer’s method for incorporating public benefits will negatively affect the clarity and transparency of these future fair use decisions. Public benefits are relevant to courts’ ultimate equitable fair use decisions, but courts must nevertheless accord the statutory considerations their due weight by engaging in the focused, factor-by-factor discussions of them that Congress provided for. While the public may benefit from a challenged use, “public benefits”—as Justice Breyer used the term—do not bear on the fourth fair use factor as codified by Congress. The fourth factor directs courts to consider “the effect of the use upon the potential market for or value of the copyrighted work.” Courts analyze this factor by investigating whether the use usurps the original work’s primary market or licensing opportunities, as well as whether the use creates a new market for the original work. “Public benefits,” meanwhile, represent non-competitive contributions to social welfare. Public benefits may include facilitating access to copyrighted works (through providing access to new users or making already-authorized users’ access more efficient); supporting the challenged user’s broader, public-oriented goals; or “promot[ing] or . . . protect[ing] the creative process.” In Oracle, the challenged use facilitated third parties’ creation of new copyright-eligible works. In any given case, therefore, public benefits represent externalities that the public is set to receive notwithstanding the challenged use’s effect on the original author’s incentives to create or its own creative expression. Justice Breyer’s public benefits analysis—necessary though it is to resolving fair use cases equitably—therefore departed from the fourth factor’s ambit. If lower courts follow his lead, the relevance of fair use’s statutory language will decrease. And if the statutory framework stops guiding fair use analysis, copyright owners and users will face greater uncertainty when predicting whether any given use will be fair, for they will no longer have a means to predict courts’ methodologies, let alone what decisions will issue. Fair use requires contextual analysis within a standardized and coherent framework. To produce greater transparency and predictability, this Note proposes reorganizing fair use analysis to isolate and incorporate public benefits as a fifth factor. Part I uses a potted history of fair use to argue that the defense exists to ensure the public reaps the maximum benefits from copyrighted works. Part II contends that existing approaches to fair use fail to adequately value public benefits deriving from challenged uses of copyrighted works. Part III proposes the five-factor framework, whereby courts would investigate public benefits as a fifth factor and then incorporate their findings into fair use’s ultimate holistic balancing. Finally, Part IV applies the new framework to Oracle to demonstrate the virtues of clearer reasoning.